Proposta de Intervenção na Oralidade: gênero relato de experiência em crianças da Educação Infantil. - Menezes, Rosângela Tavares de (2015)
In our research , we conducted an intervention in the field of orality in early childhood education class with children three years of age, considering the oral as a teaching object by its fundamental importance in the development of communication skills. Thus, we had the general objective of developing a didactic sequence based on the postulates of Schneuwly and Dolz (2011) with a view to encourage the child to use the experience account gender and consequently acquire significant discursive skills. We base our studies on Vygotsky that addresses the interrelation of thought and language, Bakhtin 's ideas aimed at language as a social activity mediated discourse genres, the concept of Marcuschi (2008) with respect to speech and writing and the study of genres, the contributions of Schneuwly and Dolz (2011) in systematizing oral teaching at school but also the ideas proposed by official documents mainly the National Curriculum Reference for Early Childhood Education on the teaching orality. The didactic intervention was held at the Municipal School, located in the city of Olinda, PE, in the month from November 2014 to May of 2015.A survey revealed that a systematization in oral teaching, and in particular the gender experience report helped the children to take ownership of its kind in discussion and possible realize the breakthrough in the development of communication skills of children who participated in this work.